Broken Angels: the Response of English Parishes to the Turkish Threat to Christendom, 1543–4 - Kitching, Christopher John (Studies in church history, 1987)
After several years’ prevarication, for diplomatic and matrimonial reasons, Henry VIII finally promised the Queen of Hungary, Regent of the Netherlands, in July 1543 (just two days before his marriage to Catherine Parr) that he would send 40,000 ducats to assist the Emperor in his fight against the Turks. It was a drop in the ocean as far as Charles V was concerned; his yearly revenue was averaging about 2¼ million ducats at this time. But that was insufficient to meet his expenses, and another 40,000 ducats was by no means to be spurned. In truth, it was modest enough too on the part of the English King as a contribution to so high a cause as the defence of Christendom, being equivalent to £10,000 sterling. But it was £10,000 which Henry could ill afford given his other commitments particularly on fortifications and military expenditure, and it seems to have been intended only as a loan, to be financed, when the logistics had been worked out, by bills drawn on London bankers and on the merchants of the staple at Calais.